Grippers in motion the fascination of automated handling tasks - Wolf, Andreas; Schunk, Henrik 1972- (Carl Hanser Verlag, 2018)
Automated gripping and handling tasks offer a great rationalization potential but they are still dificult to realize. This book shows you how to ensure process reliability on the basis of combining the right components with advanced application know-how. By explaining basic preconditions of the gripping process and highlighting the milestones of automation history, we guide you all the way through to the center of the handling process - the workpiece. Its ambient conditions and setup are clearly defined as well as the process of setting grippers in motion. Starting with simple linear movements up to multiaxis kinematics, you are provided with the details for practical solutions. A whole range of current applications illustrates the variety and opportunities of automation in daily business...